Two countries, many childhoods: meetings to create with the films Carreto and Una niña, una escuela - Omelczuk, Fernanda (2020)
Stephanie and Laura are two girls who find themselves in the uniquenessof a mode of existence that does not always have space in everyday life and schools. Tinho is sensitive enough to perceiving Stephanie’s needs as intrinsic to any child’s. Thus, a silent and complicit friendship is born between them. Laura recognizes―in her family and at the heart of the politics of the country in which she was born―that all lives matter. Every effort is therefore valid to run a school that caters for a single child.Based on the methodology for analyzing the creation of images from the Brazilian short Carreto and the Cuban short Una niña, una escuela, the article highlights the respectful way in which the directors build the relationship of children with special educational needs and their surroundings. The result of this analysis made it possible to share, inthe context of Law 13.006/2014, creative exercises based on these two films. The exercises proposed by the article, inspired by the methodology of creation pedagogy, can be developed with children, and aim to highlight Brazilian and Latin American childhoods, as well as to enhance the inventive relationship with the audiovisual material.